The relationship between coping strategies utilised by community service occupational therapists and their experience of burnout - Struwig, Nadia (My University, 2020)
Background: Occupational therapy graduates in South Africa are compelled to perform a year of Community Service before they can be independent practitioners. As novice health professionals transitioning to practice in challenging conditions, these new occupational therapists may be considered a vulnerable population, facing many stressors within the Primary healthcare system. These stressors include working in rural areas, and having limited access to physical (equipment, therapy areas etc.), professional (access to continuing professional development sessions, mentorship, networking opportunities etc.), and personal (coping skills, family support etc.) resources, which poses a challenge to providing services to clients and feeling competent as a therapist. Continuous exposure to these work-related stressors without successful ways of coping with this stress may lead to burnout. No research publications to date have described the coping strategies Community Service occupational therapists use, or how these coping strategies affect their experience of burnout. Purpose: This study sought to determine whether there is a relationship between coping strategies utilised by Community Service occupational therapists and their experience of burnout. Methods: A quantitative, descriptive, cross-sectional survey design was used. The online questionnaire included demographic information of the participants, the Maslach Burnout Inventory (which measures the three components of burnout, namely, emotional exhaustion, depersonalisation and low personal accomplishment) and the Coping Inventory for Stressful Situations (which measures forms of coping, namely, emotion-oriented coping, task-oriented coping and avoidance-oriented coping which consists of two subcomponents of avoidance and social distraction). Data collection commenced once ethical clearance was received. An invitation to participate in the online questionnaire was sent to all Community Service occupational therapists commencing Community Service in 2019 by using non-probability sampling. The questionnaire was administered via REDCap. Analysis: Data were analysed using Statistica 13.5. Frequencies and percentages were obtained for dependent and independent variables. Correlations were tested by using Spearman’s rank-order correlations. The effect of demographic variables on burnout and coping were tested using Kruskal-Wallis tests. Responses to open ended questions were coded using inductive quantitative content analysis. Results: There were 75 responses (which represented 31.92% of the CSOT population) used for the study. Around half of participants (49.33%) reported a strong support structure, with the main source of support being significant others (37.33%) and nuclear family (33.33%). Participants who reported high levels of burnout for the three components of burnout were established. Fifty five percent of participants reported high levels of emotional exhaustion, 23% reported high levels of depersonalisation and 33% reported high levels of low personal accomplishment. Most of the participants felt emotionally exhausted a few times a month(mean 3.20, SD±1.35) and most participants felt a sense of personal accomplishment at least once a week (mean 4.16, SD±0.998). The majority of participants used avoidance-oriented coping an average amount (62nd percentile), but more than task and emotion-oriented coping. Most participants reported using distraction-oriented coping falling in the 73rd percentile of the population and using social diversion coping falling in the 58th percentile of the population. Correlations using Spearman’s rank-order showed that emotional exhaustion had a low positive correlation with emotion-oriented coping (p coefficient=0.33, p<,05), suggesting that increased reports of emotional exhaustion were linked to increased use of emotion-focused coping. Depersonalisation had a low negative correlation with task-oriented coping (p coefficient=-0.396, p<,05), suggesting a link between depersonalisation and decreased use of task-oriented coping. Depersonalisation and emotion-oriented coping also had a low positive correlation (p coefficient=0.41, p<,05), suggesting that depersonalisation is linked to increased use of emotion-oriented coping. Personal accomplishment had a low positive correlation with task-oriented coping (p coefficient=0.32, p<,05), suggesting that feelings of personal accomplishment were linked to increased use of task-oriented coping. Personal accomplishment had a low negative correlation with the emotion-oriented coping (p coefficient=-0.32, p<,05), suggesting that feelings of personal accomplishment were linked to decreased use of emotion-oriented coping. Participants with strong (median=4.5, range 4.13-5.13) and adequate (median 4.12, range 3.87-4.62) support systems had a greater sense of personal accomplishment (p=0.02) and participants who reported minimal social support (median 4.67, range 4.33-4.78) reported greater levels of emotional exhaustion (p=0.01). Participants who were satisfied with the supervision they received (median 57, range 50-64.50) used social diversion to a greater extent (p=0.001) and participants who were not satisfied with the supervision they received (median 4.00, range 2.56-4.67) reported greater levels of emotional exhaustion (p=0.017). Participants who were very satisfied (median 4.75, range 4.38-5.38) and satisfied (median 4.37, range 3.94-4.88) with their jobs as CSOTs had a greater sense of personal accomplishment (p=0.0002), whereas participants who were not satisfied with their jobs experienced a greater sense of depersonalisation (p=0.047) and greater levels of emotional exhaustion (p=0.006). Conclusion: More than half (55%) of the participating CSOT population reported high levels of emotional exhaustion. Correlations between the participants’ experience of burnout and their coping strategies had low significance. A more significant relationship was found between certain demographic variables and forms of coping and components of burnout. Having strong and adequate support systems was associated with a greater sense of personal accomplishment and poor social support was associated with increased emotional exhaustion. Participants who were satisfied and very satisfied with their jobs had an increased sense of personal accomplishment while participants who were not satisfied with their jobs reported greater depersonalisation and emotional exhaustion. Decreased satisfaction with supervision was associated with increased emotional exhaustion and use of emotion-oriented coping. The importance of supporting Community Service occupational therapists in developing task-oriented coping and the avoidance of emotion-oriented coping was highlighted in the research project. Facilitating CSOTs insight into their own experience of burnout and the forms of coping they use will support their ability to develop quality services to underserved South Africans and promote their health and wellbeing which in turn helps to avoid the experience of burnout. Further research could aim at exploring the specific interventions for burnout in the CSOT population and using adaptive forms of coping at an individual and organisational level to prevent burnout
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy, 2020